Solution-processed heterojunction solar cells based on p-type PbS quantum dots and n-type Bi2S3 nanocrystals - Rath, Arup Kumar; Bernechea, Maria; Martinez, Luis; Konstantatos, Gerasimos (Advanced Materials, 2011)
Bi2S3 nanocrystals are employed as an n-type, non-toxic, inorganic, solution-processed semiconductor in thin film solar cells. The first solution processed-inorganic p-n junction based on p-type PbS QDs and n-type Bi2S3 nanocrystals with both phases contributing to photocarrier generation is demonstrated. The reported devices show a power conversion efficiency of 1.6% for 860 nm PbS QDs and over 1% for 1300 nm PbS QDs.

Solution-processed inorganic bulk nano-heterojunctions and their application to solar cells - Rath, Arup Kumar; Bernechea, Maria; Martinez, Luis; Pelayo Garcia de Arquer, F.; Osmond, Johann; Konstantatos, Gerasimos (Nature Photonics, 2012)
In the last decade, solution-processed quantum dot/nanocrystal solar cells have emerged as a very promising technology for third-generation thin-film photovoltaics because of their low cost and high energy-harnessing potential. Quantum dot solar cell architectures developed to date have relied on the use of bulk-like thin films of colloidal quantum dots. Here, we introduce the bulk nano-heterojunction concept for inorganic solution-processed semiconductors. This platform can be readily implemented by mixing different semiconductor nanocrystals in solution and allows for the development of optoelectronic nanocomposite materials with tailored optoelectronic properties. We present bulk nano-heterojunction solar cells based on n-type Bi2S3 nanocrystals and p-type PbS quantum dots, which demonstrate a more than a threefold improvement in device performance compared to their bilayer analogue, as a result of suppressed recombination.

Heterovalent cation substitutional doping for quantum dot homojunctions - Stavrinadis, Alexandros; Rath, Arup Kumar; Pelayo Garcia de Arquer, F.; Diedenhofen, Silke L.; Magen, Cesar; Martinez, Luis; So, David; Konstantatos, Gerasimos (Nature Communications, 2013)
Colloidal quantum dots have emerged as a material platform for low-cost high-performance optoelectronics. At the heart of optoelectronic devices lies the formation of a junction, which requires the intimate contact of n-type and p-type semiconductors. Doping in bulk semiconductors has been largely deployed for many decades, yet electronically active doping in quantum dots has remained a challenge and the demonstration of robust functional optoelectronic devices had thus far been elusive. Here we report an optoelectronic device, a quantum dot homojunction solar cell, based on heterovalent cation substitution. We used PbS quantum dots as a reference material, which is a p-type semiconductor, and we employed Bi-doping to transform it into an n-type semiconductor. We then combined the two layers into a homojunction device operating as a solar cell robustly under ambient air conditions with power conversion efficiency of 2.7%.

Imprinted electrodes for enhanced light trapping in solution processed solar cells - Mihi, Agustin; Beck, Fiona J.; Lasanta, Tania; Rath, Arup Kumar; Konstantatos, Gerasimos (Advanced Materials, 2013)

Determination of carrier lifetime and mobility in colloidal quantum dot films via impedance spectroscopy - Rath, Arup Kumar; Lasanta, Tania; Bernechea, Maria; Diedenhofen, Silke L.; Konstantatos, Gerasimos (Applied Physics Letters, 2014)
Impedance Spectroscopy (IS) proves to be a powerful tool for the determination of carrier lifetime and majority carrier mobility in colloidal quantum dot films. We employ IS to determine the carrier lifetime in PbS quantum dot Schottky solar cells with Al and we verify the validity of the technique via transient photovoltage. We also present a simple approach based on an RC model that allows the determination of carrier mobility in PbS quantum dot films and we corroborate the results via comparison with space charge limited measurements. In summary, we demonstrate the potential of IS to characterize key-to-photovoltaics optoelectronic properties, carrier lifetime, and mobility, in a facile way. (C) 2014 AIP Publishing LLC.

Remote trap passivation in colloidal quantum dot bulk nano-heterojunctions and its effect in solution-processed solar cells - Rath, Arup Kumar; Pelayo Garcia de Arquer, F.; Stavrinadis, Alexandros; Lasanta, Tania; Bernechea, Maria; Diedenhofen, Silke L.; Konstantatos, Gerasimos (Advanced Materials, 2014)
More-efficient charge collection and suppressed trap recombination in colloidal quantum dot (CQD) solar cells is achieved by means of a bulk nano-heterojunction (BNH) structure, in which p-type and n-type materials are blended on the nanometer scale. The improved performance of the BNH devices, compared with that of bilayer devices, is displayed in higher photocurrents and higher open-circuit voltages (resulting from a trap passivation mechanism).